2016
DOI: 10.1371/journal.pone.0162832
|View full text |Cite
|
Sign up to set email alerts
|

The Arginine/Lysine-Rich Element within the DNA-Binding Domain Is Essential for Nuclear Localization and Function of the Intracellular Pathogen Resistance 1

Abstract: The mouse intracellular pathogen resistance 1 (Ipr1) gene plays important roles in mediating host immunity and previous work showed that it enhances macrophage apoptosis upon mycobacterium infection. However, to date, little is known about the regulation pattern of Ipr1 action. Recent studies have investigated the protein-coding genes and microRNAs regulated by Ipr1 in mouse macrophages, but the structure and the functional motif of the Ipr1 protein have yet to be explored. In this study, we analyzed the domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…We observed that LM6179_RS15375/UQ65_15075 has a high concentration of lysine residues and an p I of 9.1, which suggests that the protein may interact with nucleic acids (García-García and Draper 2003 ; Yao et al . 2016 ): This is in line with other UV repair systems that alleviate UV-induced DNA damage (Crowley et al . 2006 ; Kim et al .…”
Section: Discussionsupporting
confidence: 84%
“…We observed that LM6179_RS15375/UQ65_15075 has a high concentration of lysine residues and an p I of 9.1, which suggests that the protein may interact with nucleic acids (García-García and Draper 2003 ; Yao et al . 2016 ): This is in line with other UV repair systems that alleviate UV-induced DNA damage (Crowley et al . 2006 ; Kim et al .…”
Section: Discussionsupporting
confidence: 84%
“…The highly basic Rrp6 lasso has no counterpart in prokaryotic RNase D family members ( 45 ), and appears to be a unique eukaryotic exosome-specific domain with biophysical (Supplementary Table S1) properties that appear conserved among eukaryotes (Figure 5B ), despite lacking apparent sequence conservation (Supplementary Figure S2). In addition to being highly basic, however, sequences of the apparent eukaryotic Rrp6 lassoes also share putative nuclear localization sequences, motifs that have been shown here (Supplementary Figure S6A) and elsewhere ( 46 , 47 ) to double as nucleic acid interaction motifs. Furthermore, discrete sequences within the Rrp6 lasso in yeast and metazoans may bear resemblance to other RNA binding motifs known to be in disordered regions, including lysine-rich motifs ( 48 ), and eAT-hooks ( 49 ).…”
Section: Discussionmentioning
confidence: 54%
“…We found a clustering of NFIX missense variants involving positively charged amino acids (at positions Lys 113, Arg115, Arg116, Arg121, Lys125, and Arg128) in a small region of 15 residues. Both arginine and lysine are frequently located in protein‐activating or binding sites, and their charge distribution is ideal for binding negatively charged groups (LaCasse et al., 1995; Yao et al., 2016). A putative nuclear localization (NLS) domain encompassing amino acids 36–50 of NFIX (RKRKYFKKHEKRMSK) is predicted by cNLS mapper (url: nls‐mapper.iab.keio.ac.jp/).…”
Section: Discussionmentioning
confidence: 99%
“…There is a predominant involvement of basic residues (in 12 of the 23 missense variants), and some have been altered more than once Both arginine and lysine are frequently located in protein-activating or binding sites, and their charge distribution is ideal for binding negatively charged groups (LaCasse et al, 1995;Yao et al, 2016) (Imagawa, Sakaue, Tanabe, Osada, & Nishihara, 2000). The domains are highly conserved in all NFI proteins and are located near the DNA binding domain (Imagawa et al, 2000).…”
Section: Discussionmentioning
confidence: 99%